ANTIHYPERLIPIDEMIC ACTIVITY OF METHANOLIC EXTRACT OF AZADIRACHTA INDICA - Baghel, Shalu; Singh, Charanjeet (Journal of Biomedical and Pharmaceutical Research, 2019)
Hyperlipidemia often results from delayed or defective clearance, or overproduction of VLDL by the liver, which is subsequently transformed into LDL. The whole plant of Azadirachta indica was collected from local areas of Jaipur district areas of Rajasthan. The plant is authenticated by university of rajasthan by Drmanju Sharma dept of botany Selected medicinal plant were cut into small pieces, cleaned and shade dried at room temperature then subjected to physical evaluation with different parameters. Macerated 5 g of air dried drug coarsely powdered with 100 ml of ethanol of the specified strength in a closed flask for twenty four hours, shaking frequently during six hours and allowed to stand for 18 h. About 2-3 g of powder is accurately weighed in a china dish and kept in hot air oven maintained at 110±1oC for four hours. After cooling in a desiccator, the loss in weight was recorded. This procedure was repeated till constant weight was obtained. For insoluble ash value Boiled the ash for 5-10 minutes with 25 ml of diluted hydrochloric acid, collected the insoluble matter in a Gooch crucible washed with hot water, ignited and weighed. Whole plant of Azadirachtaindicawas reduced to fine powder and was subjected to maceration in a 1 liter conical flask for 7 days at room temperature with alcohol (70%) water (30%). In the present study we aimed to screen various extracts of selected plants on Cholesterol induced hyperlipidemic rat model. Thus the results of the present investigation clearly indicated that the selected medicinal plants possess good antihyerlipidemic activity in atherogenic diet induced hyperlipidemic rats and led to the development of new Herbal formulation possessing antihyperlipidemic and antiatherosclerotic activities. This is the first study which investigates the hypolipidemic activity. Keywords: Azadirachta indica, antihyperlipidemic, antiatherosclerotic activities, Maceration.